PERGESERAN IDENTIFIKASI DAN REPRESENTASI SOSIAL (STUDI ATAS MENGUATNYA IDENTIFIKASI ADAT DI INDONESIA) - Tohari, Amin (Forum Ilmu Sosial, 2012)
This paper tries to show a shift in social identification Indonesia afterdecentralization. Identification of Indonesian society is no longer sufficientmenggunakaan read only religious or ideological basis. Post-New Ordersocial identification back to the community is the identification of a localbasis, is considered pure, and genuine. Using the case of emerging andstrengthening indigenous movement and the basis of social identificationthat is attached to it, this paper finds that indigenous movement as a politicalmovement managed to emerge and be recognized. But sentiment was used by indigenous local elite to gain importance in the local political arena. This sentiment is also a mechanism of exclusion inkulsi and other groups outside themselves relating to their rights to the resources in the area. Not infrequently he is a source of social tension. Decentralization and the emergence of social identity, citizenship melokal shows an increasinglyserious problem.